The effects of a Mycobacterium bovis infection on the metabolic and reproductive systems of African lions (Panthera leo) in the Kruger National Park. - Viljoen, Ignatius Michael (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.